The Implementation of Videoconference Codec and Consideration for Several Problems - Zhu Xiuchang; Hu Dong (Tongxin xuebao)
The construction and the characterastics in hardware design for videoconference codec inaccordance with Ref. H. 261 are described in this paper. Several crucial problems, rate control and refreshing scheme that influence the quality and stability of coded image , have been discussed,and experimental results are also presented.